Slovak Road Transport from the Point of View of Sustainable Development - Cajchan, Juraj; Ponisciakova, Olga; Poliak, Milos (Communications - Scientific letters of the University of Zilina, 2005)
In spite of the various facts transport belongs to the main contaminers of environment, therefore another transport development is contingent on conditions of permanently sustained development. The article deals with transport negative effects to the environment at present and about expected trends in the near future.